Análisis de costos de producción y propuesta de mejora para la empresa Calivan’s (2024)
In the context of the textile industry, characterized by intense competition and the need for efficient cost control, this thesis focuses on Calivan’s, a company in the sector in Colombia. The main objective is to develop a costing system that not only refines decision-making but also maximizes resource utilization. The study begins with a comprehensive diagnosis of the company's current costing processes, identifying critical areas that require improvement and establishing key points to optimize the existing costing strategy.